Primary Neurolymphomatosis of the Lower Cranial Nerves Presenting as Dysphagia and Hoarseness: A Case Report - Sakai, Naoto; Ito-Yamashita, Tae; Takahashi, Goro; Baba, Satoshi; Koizumi, Shinichiro; Yamasaki, Tomohiro; Tokuyama, Tsutomu; Namba, Hiroki (Journal of Neurological Surgery Reports, 2014)
Primary neurolymphomatosis is an extremely rare tumor. We report the case of a 74-year-old patient presenting with dysphagia and hoarseness. Initial contrast-enhanced computed tomography of the head, neck, and chest did not reveal any lesions. His symptoms improved with short-term administration of prednisone but recurred and deteriorated. Magnetic resonance (MR) imaging revealed a tumor along the ninth and tenth cranial nerves across the jugular foramen. Fluorine-18 fluorodeoxyglucose positron emission tomography indicated this was a primary tumor. Repeated MR imaging after 2 months revealed considerable tumor enlargement. A left suboccipital craniotomy was performed to remove the tumor that infiltrated the ninth and tenth cranial nerves. The histopathologic diagnosis was diffuse large B-cell lymphoma. Although focal radiation therapy was administered to ensure complete eradication of the tumor, the patient died of aspiration pneumonia with systemic metastasis. To our knowledge, this is the first reported case of primary neurolymphomatosis in the lower cranial nerves.
Keywords: cranial nerve; large B-cell lymphoma; lower cranial nerves; malignant lymphoma; neurolymphomatosis